Zabawa w teatr - profilaktyka codzienności = Play of theatre - preventive treatment of every - Sikora-Leśna, Irena (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The author presents preventive qualities of theater education. It is believed that the fun in the theater should occupy an important place in the education of children. The author shares his experiences in this area.
Keywords: cechy codzienności; zabawa w teatr; istota; działanie indywidualne; działanie grupowe; komunikacja językowa; cele i zadania; działania profilaktyczne; działania terapeutyczne; attributes of the every day reality; play of theatre; indyvidual activites; group activites; language comunication purposes and tasks; preventive and practical activites